2000
DOI: 10.1002/1522-2683(20001001)21:16<3329::aid-elps3329>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Membrane proteomics: Use of additive main effects with multiplicative interaction model to classify plasma membrane proteins according to their solubility and electrophoretic properties

Abstract: Recent efforts at the proteomic level were employed to describe the protein equipment of the plasma membrane of the model plant Arabidopsis thaliana. These studies had revealed that the plasma membrane is rich in extrinsic proteins but came up against two major problems: (i) few hydrophobic proteins were recovered in two-dimensional electrophoresis gels, and (ii) many plasma membrane proteins had no known function or were unknown in the database despite extensive sequencing of the Arabidopsis genome. In this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
118
0
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(124 citation statements)
references
References 41 publications
(42 reference statements)
3
118
0
3
Order By: Relevance
“…To analyze gene functions, new approaches have been started, including the establishment of large Arabidopsis "knock out" pop- ulations and the development of DNA chips to monitor gene expression. Meanwhile, proteome projects were initiated to systematically characterize gene products of defined subproteomes from Arabidopsis (Robertson et al, 1997;Santoni et al, 1998Santoni et al, , 2000Peltier et al, 2000). The present paper reports the initiation of an Arabidopsis mitochondrial proteome project.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze gene functions, new approaches have been started, including the establishment of large Arabidopsis "knock out" pop- ulations and the development of DNA chips to monitor gene expression. Meanwhile, proteome projects were initiated to systematically characterize gene products of defined subproteomes from Arabidopsis (Robertson et al, 1997;Santoni et al, 1998Santoni et al, , 2000Peltier et al, 2000). The present paper reports the initiation of an Arabidopsis mitochondrial proteome project.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, proteome research often is based on a subset of proteins of eukaryotic cells called "subproteome" (Cordewell et al, 2000;Jung et al, 2000). In plant biology, very successful subproteomic analyses were carried out for the cell wall, the plasma membrane, and the thylakoids (Robertson et al, 1997;Santoni et al, 1998Santoni et al, , 2000Peltier et al, 2000;Prime et al, 2000;van Wijk, 2000). During these investigations, hundreds of proteins were separated, several of which were identified for the first time.…”
mentioning
confidence: 99%
“…However, biochemical research on its protein composition is challenged by the low abundance and difficulty in handling of hydrophobic membrane proteins. Proteomic studies have identified a small number of true transmembrane proteins on two-dimensional gels (28,29). Using established protocols for the analysis of hydrophobic proteins, we obtained well resolved two-dimensional gels of carbonatewashed plasma membranes from cell cultures.…”
Section: Fig 2 Schematic Diagram Of Atsyp122 Domain Organization Anmentioning
confidence: 99%
“…For neuroscientists, this represents a challenge because many proteins of interest in the brain are expressed at relatively low levels and are hydrophobic proteins. The effectiveness of 2-DE to examine membrane proteins is limited due to poor solubilization of hydrophobic proteins (99,100). New detergents and electrophoresis methods can aid in examining hydrophobic proteins, but more improvements are needed (101).…”
Section: Limitationsmentioning
confidence: 99%